Perivascular extracellular matrix hydrogels mimic native matrix microarchitecture and promote angiogenesis via basic fibroblast growth factor. (April 2017) - Fercana, George R.; Yerneni, Saigopalakrishna; Billaud, Marie; Hill, Jennifer C.; VanRyzin, Paul; Richards, Tara D.; Sicari, Brian M.; Johnson, Scott A.; Badylak, Stephen F.; Campbell, Phil G.; Gleason, Thomas G.; Phillippi, Julie A.
Abstract: Extracellular matrix (ECM)-derived bioscaffolds have been shown to elicit tissue repair through retention of bioactive signals. Given that the adventitia of large blood vessels is a richly vascularized microenvironment, we hypothesized that perivascular ECM contains bioactive signals that influence cells of blood vessel lineages. ECM bioscaffolds were derived from decellularized human and porcine aortic adventitia (hAdv and pAdv, respectively) and then shown have minimal DNA content and retain elastin and collagen proteins. Hydrogel formulations of hAdv and pAdv ECM bioscaffolds exhibited gelation kinetics similar to ECM hydrogels derived from porcine small intestinal submucosa (pSIS). hAdv and pAdv ECM hydrogels displayed thinner, less undulated, and fibrous microarchitecture reminiscent of native adventitia, with slight differences in ultrastructure visible in comparison to pSIS ECM hydrogels. Pepsin-digested pAdv and pSIS ECM bioscaffolds increased proliferation of human adventitia-derived endothelial cells and this effect was mediated in part by basic fibroblast growth factor (FGF2). Human endothelial cells cultured on Matrigel substrates formed more numerous and longer tube-like structures when supplemented with pAdv ECM bioscaffolds, and FGF2 mediated this matrix signaling. ECM bioscaffolds derived from pAdv promoted FGF2-dependent in vivo angiogenesis in the chick chorioallantoic membrane model. Using an angiogenesis-focused protein array, we detected 55 angiogenesis-related proteins, including FGF2 in hAdv, pAdv and pSIS ECMs. Interestingly, 19 of these factors were less abundant in ECMs bioscaffolds derived from aneurysmal specimens of human aorta when compared with non-aneurysmal (normal) specimens. This study reveals that Adv ECM hydrogels recapitulate matrix fiber microarchitecture of native adventitia, and retain angiogenesis-related actors and bioactive properties such as FGF2 signaling capable of influencing processes important for angiogenesis. This work supports the use of Adv ECM bioscaffolds for both discovery biology and potential translation towards microvascular regeneration in clinical applications.